Skeletal muscle signature of elite master endurance runner with thalassemia - a case study - Strelecky, M.; Sedliak, M.; Berisha, G.; Oreská, L.; Buzgo, G.; Cernácková, A.; Okuliarova, M.; Zeman, M.; Kern, H.; Zampieri, S.; Pietrangelo, L.; Protasi, F. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Thalassemia is a type of inherited hemoglobinopathy resulting in reduced ability to produce haemoglobin. Depending on a type of thalassemia, endurance performance may be negatively affected but there is lack of evidence in master athletes. We had a unique opportunity to examine not only performance and blood parameters but also skeletal muscle characteristics of an elite male master marathon runner who placed second at the World championship in the age category 75-79 years and won all the World Marathon Majors between 2013 and 2019. METHODS: A 79-year-old Caucasian male (body height 168.2 cm, body mass 59.5 kg, BMI 21 kg/m2) with hereditary form *-thalassemia voluntarily participated in this study. The data were collected throughout the 3 weeks. During the first week, maximal isometric voluntary contraction (MVC) of the knee extensors and incremental laboratory exercise test to on a bicycle ergometer for VO2max were performed. During the second week, the subject was instructed to maintain his habitual daily activities. During the third week on Tuesday, the subject underwent a blood sampling procedure and muscle biopsy for histological analyses. All data were compared to earlier results from our laboratory. RESULTS: As expected, blood count showed abnormalities in hemoglobin values (106 g/l, reference range (r.r.) 135-172 g/l), haematocrit (0.33% r.r. 0.42-0.52%), MCV (64.2 fl, r.r. 84-98) and MCH (20.7 pg r.r. 28-34), Serum iron concentration, its binding capacity, ferritin, and transferrin were within the normal range. Histology - the individual´s mean myofiber diameter values (58.60 ± 13.92 µm) very similar to that observed in young adult, and higher in comparison to that observed in aged-matched sedentary elderlies. The two type-groupings refer to reinnervation events and circulating levels of C-terminal agrin fragment as a biomarker of neuromuscular junction destabilization was lower than in aged matched sedentary elderlies (5623 pg/ml vs 6350,7 pg/ml). Electron microscopy - the high mitochondria number (more than doubled if compared to sedentary seniors of the same age) was not accompanied by a parallel marked increase in their volume and a small average size of these organelles is reported. Taken together these factors suggests that possibly mitochondria are undergoing active fission processes. In bilateral knee extension and flexion, the MVC values were 138.2 Nm and 34.91 Nm/kg, respectively. The predicted VO2max value was 44.3 ml/kg/min. CONCLUSION: Despite the thalassemia and impaired parameters of blood count, the performance and muscle tissue quantitative and qualitative measures were well preserved in the elite master marathon runner. Moreover, analysed muscle tissue was in several aspects more similar to young men than to the subjects` age-matched sedentary counterparts.